The experience of Italian student athletes enrolled in a dual career university program: the challenges of employability - Belluzzi, Mattia; Ferraboli, Alessia; Gozzoli, Caterina; D’Angelo, Chiara (Frontiers in Sports and Active Living, 2025)
IntroductionIn the so-called “new career era,” career transitions and employability have attracted growing attention. For elite athletes, the Dual Career experiences may be regarded as a protective factor during various career transitions, with the end-of-career transition being closely linked to employability. This contribution aims to explore the dual career paths of athletes through the lens of graduate employability, as perceived by the individuals themselves. Thus, employability can be considered as an important resource for athletes during the many transitions that characterize their sports careers.MethodologyStudy participants included 21 student-athletes participating in the first four editions of the Dual Career program at an Italian university. Using a phenomenological-interpretive approach, semi-structured interviews and focus groups were conducted with participants. A top-down and bottom-up content analysis was conducted using Nvivo software for qualitative analysis.ResultsThe data derived from interviews and focus groups are presented with reference to four dimensions—Human Capital, Social Capital, Individual Behaviors, and Individual Attributes—that, according to Clarke's integrated model, impact perceived employability in graduate students, including student-athletes. The results highlight traits shared with classic university students while, at the same time, emphasizing peculiar sub-dimensions.DiscussionThis study integrates the constructs of employability and career transitions in the target group of university athletes. Through the Clarke's model, which offers a complex and multidimensional definition of employability, this research explores why the dual career pathway represents a resource for athletes during transitions. The results can serve as a first step in developing good practices for supporting and guiding student-athletes enrolled in Dual Career programs, by addressing aspects recognized in the scientific literature as practical implications for supporting employability development.